Analysis of the glued wood joint / Kamarul Azian Hashim - Hashim, Kamarul Azian (1993)
The objective of this study is to analyse the glued wood joint of glued laminated timber beam with a different cross section and lap lengths. The analysis is to obtain the stresses in and around the joint using the ANSYS program package for the selected types of the model.